Aggregation of microplastics and clay particles in the nearshore environment: Characteristics, influencing factors, and implications. (1st October 2022) - Yang, Xiaohan; An, Chunjiang; Feng, Qi; Boufadel, Michel; Ji, Wen
Highlights: Clay particles can affect the aggregation and settling behaviors of microplastics. The aggregation behaviors vary under different nearshore environmental conditions. Aggregation behavior is driven by the repulsive energy barrier and external energy. Wave energy plays an important role in aggregations for a nearshore context. The deposition analysis demonstrates the shoreline is the sink for microplastics. Abstract: Since nearly half of the world's population lives near the coast, coastal areas have become hotspots for microplastic (MP) pollution due to human activity. The ubiquity of natural colloids in coastal waters plays a critical role in the potential fate of, and risks posed by, MPs. Nevertheless, far less has been known regarding the aggregation of MPs with inorganic natural clay colloids, especially in the complicated nearshore environment. In this study, the aggregation behavior of MPs as well as the interaction between MPs and clay particles were investigated under different nearshore environmental conditions (MP-to-clay ratio, salinity gradient, humic acid concentration, and wave energy). The aggregation behavior was subjected by the repulsive energy barrier between particles and external energy transferred to the system. The low energy associated with mild wave conditions was favorable for the occurrence of aggregation, whereas sustained high energy under intense wave conditions was found to be detrimental to the aggregation behavior, and the aggregates were prone to fragmentation even if particles coalesced into large clusters. The analysis for the environmental fate of MPs demonstrated that the shoreline was likely to be the sink for most MPs ultimately. Graphical abstract: Image, graphical abstract